Sir Nicholas Bacon and the Elizabethan via media - Collinson, Patrick (The historical journal, 1980)
There exists in the British Museum a copy of the prayer book of 1559 bearing the signature of Sir Nicholas Bacon. It would be reasonable to infer that the book was once the lord keeper's property, but a pleasing fancy to pretend that he autographed it for a friend and well-wisher. He was not the author of this all but final recension of the Anglican liturgy but he was one of its principal sponsors. For in the words of Ralph Churton,’the business of that important parliament… in which the acts of uniformity and supremacy for the settlement of religion were passed was principally managed by the Lord Keeper Bacon’. It was Bacon who presided, not only in the House of Lords but over the theological disputation in Westminster Hall which was staged as a public signal that the English Church was to be once more reformed according to the protestant model. In a speech at the conclusion of the 1559 parliament he defended the newly made settlement against opponents and detractors, and in so doing scratched in the sand, as it were, the line of the Anglican via media:’Amongst thease I meane to comprehende aswell those that be to swifte as those that be to slowe, those I say that goe before the lawe or beyond the lawe as those that will not followe.’